## 4x + 3y = 12 2x + 3y = -6 select each correct answer

Question

4x + 3y = 12 2x + 3y = -6 select each correct answer

in progress 0
2 months 2021-07-28T01:09:58+00:00 1 Answers 1 views 0

(9, -8)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

1. Brackets
2. Parenthesis
3. Exponents
4. Multiplication
5. Division
7. Subtraction
• Left to Right

Equality Properties

• Multiplication Property of Equality
• Division Property of Equality
• Subtract Property of Equality

Algebra I

• Solving systems of equations using substitution/elimination

Step-by-step explanation:

Step 1: Define Systems

4x + 3y = 12

2x + 3y = -6

Step 2: Rewrite Systems

4x + 3y = 12

1. Multiply everything by -1:                    -4x – 3y = -12

Step 3: Redefine Systems

-4x – 3y = -12

2x + 3y = -6

Step 4: Solve for x

Elimination

1. Combine 2 equations:                     -2x = -18
2. Divide -2 on both sides:                  x = 9

Step 5: Solve for y

1. Define equation:                     2x + 3y = -6
2. Substitute in x:                        2(9) + 3y = -6
3. Multiply:                                   18 + 3y = -6
4. Subtract 18 on both sides:      3y = -24
5. Divide 3 on both sides:           y = -8